Study on status of gas pipeline safety management in Jiangmen City in China - LI, Yang (IJRDO - Journal of Applied Management Science, 2019)
With the rapid development of China's economy and the vigorous advancement of urbanization, the use of gas as a clean and environmentally friendly energy source is increasing year by year. At the same time, the safety of urban pipeline gas has become increasingly prominent. Through research, it is found that the main reasons for the application of urban gas are: brutal construction of construction units, occupational pressure pipelines for residents, corrosion of pipelines, and aging of gas stoves for residents. In response to the above problems, Jiangmen China Resources Gas Co., Ltd. has explored and developed an effective operation of the city gas safety management system, namely the maintenance of gas pipeline safety and safety risk monitoring, the combination of government policies and corporate supervision, and a risk prevention and early warning system. Through the active cooperation of all departments, the city gas can operate safely and effectively.